5+3t-3=8t+14-3t

Simple and best practice solution for 5+3t-3=8t+14-3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3t-3=8t+14-3t equation:


Simplifying
5 + 3t + -3 = 8t + 14 + -3t

Reorder the terms:
5 + -3 + 3t = 8t + 14 + -3t

Combine like terms: 5 + -3 = 2
2 + 3t = 8t + 14 + -3t

Reorder the terms:
2 + 3t = 14 + 8t + -3t

Combine like terms: 8t + -3t = 5t
2 + 3t = 14 + 5t

Solving
2 + 3t = 14 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
2 + 3t + -5t = 14 + 5t + -5t

Combine like terms: 3t + -5t = -2t
2 + -2t = 14 + 5t + -5t

Combine like terms: 5t + -5t = 0
2 + -2t = 14 + 0
2 + -2t = 14

Add '-2' to each side of the equation.
2 + -2 + -2t = 14 + -2

Combine like terms: 2 + -2 = 0
0 + -2t = 14 + -2
-2t = 14 + -2

Combine like terms: 14 + -2 = 12
-2t = 12

Divide each side by '-2'.
t = -6

Simplifying
t = -6

See similar equations:

| (X+14)=(x-20) | | 25=2(x+3) | | 2x+2(x-28)=-104 | | 2x-1-x=9x-3 | | -18+10=-17s | | (x+4)(x-4)=4 | | 5+y=0.0024x | | 3x+2(x-28)=-104 | | y=3x^2-6x+200 | | 2x-8(2x-8)=44 | | 25u+75=23u+92 | | (X+10)=(x-11) | | -7-0.83x=18 | | 4x+b=ax+9 | | (X-11)=(2x-42) | | 16x=180+12y | | .8v+3.2=2.4-v | | (X+10)=(2x-42) | | 2x+5-x=3(2-x)+7 | | 9x-55=110-2x | | -(1+6m)-8=-7(m+1) | | 3x-6x-11=-3x+3-11 | | 2.5x=9.5 | | 3(-0.9n+0.5)=-3.5+1.3 | | -5a^2-8=-5a | | -4(3x-3)+9=-12x+21 | | 38+38+4x=180 | | (5y+8)-(5+4y)=8 | | 3(x-2)=4(x+2) | | 8z^3-16z^2=0 | | 20+yi=11-x+7i | | 48+90+7x=180 |

Equations solver categories